SPONGE MOLECULAR SCREENING FOR ANTIMICROBIAL GENES BY PCR - Rosmiati Rosmiati; Emma Suryati; Andi Parenrengi; Sulaeman Sulaeman (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2007)
Molecular biotechnology approach has been applied on sponge for preventingdiseases on fishery culture. This is important for anticipating and avoiding the using of amount of sponge in nature. The present study aims to screen the antimicrobial (oxytetracycline and chloramphenicol) genes of sponge. DNA extraction of samples was done using the DNeasy Plant mini kit, Phenol-Chloroform and modification of Phenol-Chloroform methods. The presence of oxytetracycline and chloramphenicol genes in sponge was detected using Polymerase chain reaction (PCR) technique. Result of the study showed that four species (Sylotella aurantium, Acanthella kletra, Gelliodes fibulatus and Auletta sp. were amplified for oxytetracycline and two species (Auletta sp. and Pericharax sp.) of sponge were amplified for chloramphenicol at each 226 bp.